La disregolazione percettiva nell'autismo e potenzialità terapeutica dell'intelligenza artificiale - Maria Provenzale (Marp Edizioni, 2021)
The complexity of the clinical picture characterizing neurodevelopmental disorders opens up a vast and heterogeneous field of study in which the sense-perceptual development of autistic subjects represents one of the areas of greatest clinical interest, given that the sense-perceptual dysregulation of autistic pathology affects in a way particularly the expression of intersubjectivity. Much of the neurocognitive and behavioral deficits associated with autistic disorder can, in fact, be explained by an alteration in the sense-perceptive regulation of environmental stimuli that normally allow the individual to relate to his environment, therefore contact with reality and with everything that surrounds it. The developments in neuroscience are configured in the intervention of autism in a multidimensional vision that evaluates the numerous variables that come into play in the production of the behavioral response, in which cognitive, emotional, physiological, relational and psychological aspects are intertwined and inseparable. For this reason it is appropriate that the different intervention models in the field of autism work on several levels to offer an approach that is as integrated as possible, thanks also to the support provided by the new therapeutic horizons represented by the use of technological aids to support of cognitive disability in general. The complexity of autistic pathology therefore requires from the scientific community a strong attention to the integration of different intervention models and clinical tools, in which the development of artificial intelligence can be seen as a precious resource for the treatment of autism: it is focused in particular on the cognitive resources of the subject, capable of mediating the expression of more adequate behavioral responses, in terms of functionality and effectiveness, reducing the relational distance between the autistic child and his / her social network.